Melchiorre Gioia e il diritto penale - Massetto, Gian Paolo (Acta Histriae, 2007)
The paper aims to present the premises concerning penal law provided by a series of relatively short writings published by Melchiorre Gioia at the end of the 18th and beginning of the 19th centuries, as well as by some of his interlocutors, with whom the author from Piacenza engaged in harsh debates. Given their nature, these writings have already been a subject of research interest in the fields of statistics, and political and economic history; however, being rich with significant reflections, evaluations, and observations concerning penal law, they also stir the interest and curiosity of legal historians
Keywords: 19.st.; Gioia, Melchiorre; gospodarska zgodovina; javna uprava; Lombardija; pravna zgodovina; primary source; zgodovinski viri